Rotor speed, load torque and parameters estimations of a permanent magnet synchronous motor using extended observer forms. Issue 9 (1st June 2017) - Tami, Ramdane; Boutat, Driss; Zheng, Gang; Kratz, Frédéric; El Gouri, Rachid
Abstract : This study presents a new approach to estimate states and parameters of the permanent magnet synchronous motor (PMSM) in the presence of unknown load torque disturbance. Indeed, it highlights an auxiliary dynamics that is added to the PMSM model. Thereby, it supplies a change of coordinates that transforms the extended model (PMSM model together with the auxiliary dynamics) into the so‐called extended non‐linear observer forms. It turns out that the obtained form provides two observer normal forms. One of them supports the well‐known high‐gain observer which is used to estimate the speed and the unknown load torque. The second one which is affine in the parameters enables us to estimate simultaneously the states and motor parameters by means of an adaptive observer. The performance of the proposed method is illustrated by the simulations results.